2008
DOI: 10.1021/jp8000256
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pressure on Silicon Nanowire Growth Kinetics

Abstract: Si nanowire growth kinetics was studied, and the growth rate was shown to be highly sensitive to SiH4 precursor pressures, changing from a second-order dependence at low pressures to first-order and then independent at high pressures. Molecular collisions of SiH4 with He carrier gas account for this finding. The second- and first-order correlation was explained by the unimolecular reaction model and the saturated growth rate was due to the Langmuir adsorption limit. Our results suggest that precursor pressures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…The dependence on P Total will depend on how the P s varies with P Total as observed by Zhao et al 31 Growth rate has been experimentally observed to vary parabolically and linearly with P Total in both confined, i.e., within templates and non-confined cases. 5,14,31…”
Section: Pressure Dependencementioning
confidence: 82%
“…The dependence on P Total will depend on how the P s varies with P Total as observed by Zhao et al 31 Growth rate has been experimentally observed to vary parabolically and linearly with P Total in both confined, i.e., within templates and non-confined cases. 5,14,31…”
Section: Pressure Dependencementioning
confidence: 82%
“…The reaction was performed at 475 °C with 60 sccm (standard cubic centimeters per minute) of SiH 4 gas fl ow (10% in He, Airgas) and 30 sccm of H 2 co-fl ow. To achieve different growth kinetics, the pressure was varied from 5 to 50 Torr [12].…”
Section: Sinws Growthmentioning
confidence: 99%
“…Next, we turned our attention to the growth kinetics. We recently reported that the growth rate of SiNWs is sensitive to the total pressure [12]. Based on this control of growth, we systematically studied the microstructures of SiNWs grown under different rates, from as slow as ~20 nm/min to as fast as ~1300 nm/min (Fig.…”
Section: Nano Researchmentioning
confidence: 99%
“…1 Various methods have been developed to synthesize SiNWs, among which chemical vapor deposition ͑CVD͒ offers advantages such as excellent control over quantity, quality, diameter, and length of the nanowires. [1][2][3][4][5] Existing SiNW CVD growth, however, usually requires temperatures above 400°C, depending on the gas precursors and growth seed materials used.…”
Section: Low-temperature Synthesis Of Si Nanowires Using Multizone Chmentioning
confidence: 99%